The Utilization of Digital Media in Islamic Religious Education Learning: Challenges and Implementation Strategies - Ratih Gumilang; Afifah Az Zahra; Muhamad Rifai; Benny Prasetiya (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
This study aims to analyze the forms of digital media utilization in Islamic Religious Education (IRE), identify the challenges encountered in its implementation, and examine implementation strategies that can be applied within the Indonesian educational context. The study employed a qualitative approach using a library research method. Data were collected through a review of various relevant literature sources, including scientific journal articles, books, conference proceedings, and other academic documents. Data analysis was conducted using content analysis through the processes of data collection, reduction, interpretation, and conclusion drawing. The findings indicate that the digital media commonly utilized in Islamic Religious Education include instructional videos, Learning Management Systems (LMS), educational applications, e-books, and social media platforms. The use of digital media has been shown to enhance students’ learning motivation, expand access to learning resources, and promote more active and independent learning experiences. However, its implementation continues to face several challenges, including limited technological infrastructure, inadequate digital competencies among teachers, disparities in internet access, and the risk of misuse of digital information. Therefore, efforts to optimize the utilization of digital media in Islamic Religious Education require the enhancement of educators’ digital competencies, the strengthening of technological facilities and infrastructure, and the integration of digital literacy and Islamic values into the learning process. These strategies are expected to support the effective implementation of digital media and contribute to improving the quality of Islamic Religious Education in the era of digital transformation.